LEARNER AGENCY, ENGLISH PROFICIENCY, AND LEARNING BEYOND THE CLASSROOM: LESSONS FROM TEN ADVANCED EFL LEARNERS - Lu, Meiyu (LLT Journal: A Journal on Language and Language Teaching, 2024)
Within the framework of sociocultural theories, this study investigated how affordances in various beyond the classroom settings supported the development of agency and English proficiency among advanced EFL learners. The participants were 10 Taiwanese college students, each with at least B2 proficiency according to the Common European Framework of Reference for Languages. Data were gathered through a qualitative approach encompassing semi-structured interviews, writing samples, and a 23-item questionnaire. A grounded theory approach was adopted to analyze and interpret the data. The findings revealed that contextual affordances were not always immediately accessible or apparent to learners and exhibited considerable variability across different locations, which could impede or facilitate the learners’ development of agency and English proficiency. The mediator played an indispensable role in guiding learners toward effectively utilizing these resources. Furthermore, the development of learners' English proficiency in beyond-the-classroom settings was intricately intertwined with that of their agency, both of which were deeply rooted in and shaped by sociocultural contexts. As learners enhanced their English proficiency through the mediator’s strategic engagement with contextual affordances, their agency concurrently flourished, prompting them to proactively seek additional affordances and explore further opportunities for autonomous decision-making and action.